In vitro antileishmanial activity of tryptophanol derivatives - Cortes, S (2024)
Leishmaniasis is a vector borne disease (VBD) caused by protozoan parasites of the genus Leishmania and still one of the Neglected Tropical Disesases (NTDs) causing more than 1 million cases/year worldwide. Current treatments have significant drawbacks in terms of efficacy, safety, compliance, and suitability for use in the field, with growing resistance in clinical isolates, indicating the urgent need for new therapeutic options. In recent years indole-based compounds have been explored as potential antiparasitic agents and indole nucleus has emerged as a privileged molecular scaffold for the generation of new drug candidates. In this study, a small library of 14 indole compounds - tryptophanol derivatives - was synthetised and explored for its antiparasitic potential against Leishmania parasites. Leishmania infantum and L. tropica promastigote and intracellular amastigote forms, as well as oxidative stress, were used to test the compounds' in vitro antileishmanial activities. Assessments of cytotoxicity were also conducted on mammal cells (THP1 cell line). The anti-leishmania promastigotes activity produced by these drugs ranged from 100 to 7.3 µM in terms of IC50. Compounds RJ59 and PAF92 induced ROS production, had low cytotoxicity, with good activity in intracellular amastigotes (IC50 20-6 µM). Based on these preliminary results, a new set of derivatives from these two compounds was synthesized by introducing different type of substituents in the main scaffold. Susceptibility of L. infantum promastigotes appear to significantly increase with very good safety profiles. More studies are ongoing support the relevance for further investigations of this class of compounds in the context of leishmaniasis therapy. Acknowledgements: This work was supported by National Funds (Fundação para a Ciência e a Tecnologia) through iMed.ULisboa (UIDB/04138/2020), project PTDC/QUI-QOR/1304/2020 GHTM (UID/04413/2020), LAREAL (LA/P/0117/2020), PhD fellowship 2022.11539.BD (R. Ferreira) and CAPES/PRINT(Brazil)-project 88887.915934/2023-00 (L. Braz)